$x_{n+2}\begin{cases}3x_{n+1} + 2=3(2x_n+1)+2=6x_n+5&n\text{ is odd}\\ 2x_{n+1}+1=2(3x_n+2) +1=6x_n+5&n\text{ is even}\end{cases}=6x_n+5$
Así que $x_1= 1$ . $x_3 = 6*1+5; x_5 = 6(6*1+5)+5 = 6^2 + 6*5 + 5; x_7=6^3+ 6^2*5 + 6*5 + 5$ .
Así que por inducción $x_{2n-1}= 6^{n-1} + 6^{n-2}*5 + 6^{n-3} + ..... + 6*5 + 5=$
$6^{n-1} + 5(6^{n-2} + ...... + 1)=$
$6^{n-1} + 5\frac {6^{n-1} -1}{6-1} = $
$6^{n-1} + 6^{n-1}-1=2*6^{n-1}-1$ .
(Ejemplo: $x_5=x_{2*3 -1} = 2*6^2 -1 =71$ y, de hecho, $x_1 = 1; $ x_2=3; x_3=11;x_4= 2 11+1=23; x_5 = 3 23+2 = 71$.)
Igualmente $x_2 = 3;x_4 = 6*3 + 5$ et $x_6= 6^2*3 + 6*5 + 5$ et $x_{2n} = 6^{n-1}*3 + 5(6^{n-2}+... + 1)=$
$6^{n-1}*3 + 5\frac{6^{n-1}-1}{6-1}= 6^{n-1}*4 - 1$ .
(por ejemplo $x_6=x_{2*3} = 6^2*4-1 = 143$ et $x_5=71$ así que $x_6=2*71 + 1 = 143$ )
Y eso es todo:
Así que $\lim_{2n\to \infty} \frac {\log x_{2n}}{2n} = \lim_{2n\to \infty}\frac {\log (4*6^{n-1} -1)}{2n}=$
$\lim_{2n\to \infty}\frac {\log 4*6^{n-1} }{2n}=\lim_{n\to \infty}\frac {(n-1)\log 6 + \log 4}{2n}=$
$\lim_{2n\to \infty}\frac {n-1}{2n}\log 6 = \frac {\log 6}2$ .
así que $\lim_{n\to \infty; n\text{ even}}\frac {\log x_n}n = \frac {\log 6}2$ .
Y $\lim_{2n-1\to \infty} \frac {\log x_{2n-1}}{2n-1} = \lim_{2n-1\to \infty}\frac {\log (6^{n-1} -1)}{2n-1}=$
$\lim_{2n-1\to \infty}\frac {\log 6^{n-1} }{2n-1}=\lim_{2n-1\to \infty}\frac {(n-1)\log 6 }{2n+1}=$
$\lim_{2n-1\to \infty}\frac {n-1}{2n-1}\log 6 = \frac {\log 6}2$ .
Así que $\lim_{n\to \infty; n\text{ odd}}\frac {\log x_n}n = \frac {\log 6}2$